Políticas do turismo e a sustentabilidade sócioambiental em Moçambique: a experiência das áreas prioritárias para o investimento turístico e seus impactos no município de Inhambane - Fernando, Mamerto (2013)
This research aims to reflect on the relationship between people and the environment in the process of tourism development in Mozambique, from the analysis of public policy and the social and environmental impacts of tourism development in priority areas for tourism investment, with emphasis for major changes occurring in different natural ecosystems and the changes in the social structure of the peripheral communities of the study area. To this end, the study area is the coastline of Tofo and Barra in the Inhambane city, in Inhambane province, southern Mozambique. The tourism in this area is one of the major socio-economic activities, what makes the Inhambane city and the beaches of Tofo and Barra in particular, a national, regional and international preference, due to its diversity of tourism and the progressive growth of tourism infrastructure which in turn associated with tourism demand have strong environmental impacts, particularly in the coastal zone characterized by primary dunes and a diversity of marine and coastal sensitive ecosystems. Due to the characteristics and marine biodiversity in the region, tourism of sun and beach, diving and sport fishing are great reference site, where you can observe several rare species, including whales, sharks, dolphins and other species in one place. The occupation of spaces for tourism occurred sporadically and disorderly creating serious social and environmental impacts, erosion where it appears as the most serious and so far the local municipality does not yet have a concrete plan of arrangement that can tour disciplinary current land occupations and minimize environmental risk. For a better understanding of the scenarios studied, it was important to analyze the Mozambican legislation on tourism and the environment and contact with different public institutions involved in the process of tourism development, since the allocation of land for tourism and licensing activity. Henceforth, from the on-site survey was able to detect the main environmental impacts that occur on site that are associated in some way to the fragility of the public sector in the process of participatory planning for sustainable tourism.